Evaluation of Manning’s Coefficients for the Al-Adhaim River Basin in Iraq utilizing Modern Techniques - Alrammahi, Faris Sahib; Al-Madhlom, Qais Hatem Mohammed; Jassim, Sanaa Abdulrazaq (Engineering, Technology & Applied Science Research, 2025)
The current study presents an innovative analysis that combines climate and land use data to assess changes in Manning’s coefficient within the Al-Adhaim River Basin (ARB) from 2017 to 2023. The primary objective is to calculate the hydraulic roughness coefficient (Manning coefficient, n) and evaluate its variations in relation to climate and land use changes. The ArcGIS and HEC-RAS software were utilized for the spatial and hydraulic analysis, respectively, as well as to calculate the arithmetic average for the entire study area. The results indicate an increase in temperature, humidity, and rainfall of 0.82 oC, 1.07 g/kg, and 0.41 mm/year, respectively, with a decrease in wind speed of 0.02 m/s. These climatic changes contributed to a 3.96% increase in crop area, while human activities led to a 0.72% rise in built areas and a 3.93% reduction in open areas. Manning’s coefficient, despite its low value of 0.0695, demonstrated a strong relationship between its value and the aforementioned factors.